Synthesis and Electrochemical Performances of Iron Oxalate-Multiwalled Carbon Nanotubes Composite Anode for Lithium-ion batteries. Issue 2 (March 2021) - Li, Yongjia; Gao, Geng; Wang, Qianwen; Zhang, Keyu; Yao, Yaochun
Abstract: Iron oxalate, a widely used anode material in lithium-ion batteries for nearly 10 years, has been developed as promising candidates for anode materials owning to their higher electrochemical reactivity, outstanding cyclability, lower cost and environmental friendliness. In this paper, the iron oxalate-multiwalled carbon nanotubes (FeC2 O4 @C) composite was successfully synthesized by electrostatic self-assembly technique and the influence of special structure on lithium storage ability was also explored. The results show that the multiwalled carbon nanotubes are embedded inside the rod-like particles of FeC2 O4 and also threaded on surface of the multilayer structure. Coupled with excellent structural stability and enhanced Li + ion diffusion coefficient, FeC2 O4 @C exhibits suggests superior long-term stability (a reversible specific capacity of 970 mAh g −1 after 50 cycles at 0.5 A g −1 ) and satisfactory rate capability (824.06 mAh g −1, 770.47 mAh g −1 and 688.60 mAh g −1 at 1, 2, 3 and 5 A g −1, respectively).